Pemodelan Aplikasi Pengelolaan Data Wajib Pajak Menggunakan Pendekatan SDLC - Siregar, Kalfida Eka Wati; Fadil, Ulfi Muzayyanah; Armansyah, Armansyah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2025)
Efficient and accurate taxpayer data management is very important in supporting tax administration.However, the data management system used in Tuntungan 1 Village currently still relies on traditional methodsthat are less integrated, thus limiting the efficiency and accuracy in managing taxpayer data. This study aims todesign a taxpayer data management information system model using the Software Development Life Cycle (SDLC)approach and prototype method. The SDLC stages include planning, user needs analysis, and model design withUML diagrams that map the process flow and interactions between system components clearly and systematically.The results of the study are in the form of a comprehensive information system model, which is expected to increaseefficiency and accuracy in managing taxpayer data. Based on the evaluation, this system model shows a feasibilityvalue of 87%, which indicates good potential to be applied in supporting more structured and integrated taxpayerdata management.